2018
DOI: 10.1083/jcb.201803127
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Hsp90 availability reveals differential coupling to the heat shock response

Abstract: Alford and Brandman quantify the ability of the Hsp90 chaperone system to fold its client proteins and describe how loss of this functionality affects the heat shock response. They find that the heat shock response responds to diverse defects in protein quality by monitoring the state of multiple chaperone systems independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Our results put previous observations from high-throughput studies on connections between Hgh1, Cns1, eEF2, and Hsp90 (Alford and Brandman, 2018;Brandman et al, 2012;McClellan et al, 2007) into context. Interestingly, Hgh1 was also shown to be involved in stress granule formation (Cherkasov et al, 2015), a process that is connected to translation elongation.…”
Section: Discussionsupporting
confidence: 79%
“…Our results put previous observations from high-throughput studies on connections between Hgh1, Cns1, eEF2, and Hsp90 (Alford and Brandman, 2018;Brandman et al, 2012;McClellan et al, 2007) into context. Interestingly, Hgh1 was also shown to be involved in stress granule formation (Cherkasov et al, 2015), a process that is connected to translation elongation.…”
Section: Discussionsupporting
confidence: 79%
“…Several genes had strong interactions in some stressors but not others. For example, knockdown of the Hsp90 co-chaperone Sti1 (Chang et al, 1997;Nicolet and Craig, 1989) had aggravating interactions specifically with macbecin and canavaine, two stressors which have been demonstrated to reduce Hsp90 availability (Alford and Brandman, 2018) , and unexpectedly, bortezomib ( Figure 5C). Knockdown of GCN3, a gene involved in translation initiation regulation (Yang and Hinnebusch, 1996) , had the strongest aggravating interactions in the screen, hyperinducing the response to hydrogen peroxide, amino acid starvation, and arsenite stress.…”
Section: Reporterseq Reveals Stress-specific Hsr Regulatorsmentioning
confidence: 97%
“…Indeed, it has been previously reported that AZC can cause aggregation of endogenous proteins (Weids and Grant 2014), and that aggregation can be a mechanism for avoiding degradation (Wallace et al 2015). Because canavanine and AZC robustly activate the HSR, a response that is driven by a drop in protein chaperone availability (Zheng et al 2016;Alford and Brandman 2018), we reasoned that chaperones become limiting under folding stressors and this may drive protein aggregation. To test this, we boosted Hsf1 activity to increase chaperone levels and determined if this would increase the stability of our degron reporters during canavanine and AZC treatment.…”
Section: Folding Stressors Cause Aggregation and Results In Failure Tomentioning
confidence: 97%
“…an indirect proteasomal stress), transcriptional activation of RPN4, or both. Indeed, canavanine and AZC robustly activate Hsf1, a transcriptional activator of RPN4 (Hahn, Neef, and Thiele 2006;Yamamoto et al 2008;Alford and Brandman 2018). We therefore investigated the role of transcriptional regulation of RPN4 in activating the PSR during stressor treatment.…”
Section: Folding Stressors Activate the Psr Exclusively Via Transcripmentioning
confidence: 99%